Genetic dissection of branch architecture in oilseed rape (Brassica napus L.) germplasm - Wang, Ying; Wang, Kaixuan; An, Tanzhou; Tian, Ze; Dun, Xiaoling; Shi, Jiaqin; Wang, Xinfa; Deng, Jinwu; Wang, Hanzhong (Frontiers in Plant Science, 2022)
Branch architecture is an important factor influencing rapeseed planting density, mechanized harvest, and yield. However, its related genes and regulatory mechanisms remain largely unknown. In this study, branch angle (BA) and branch dispersion degree (BD) were used to evaluate branch architecture. Branch angle exhibited a dynamic change from an increase in the early stage to a gradual decrease until reaching a stable state. Cytological analysis showed that BA variation was mainly due to xylem size differences in the vascular bundle of the branch junction. The phenotypic analysis of 327 natural accessions revealed that BA in six environments ranged from 24.3° to 67.9°, and that BD in three environments varied from 4.20 cm to 21.4 cm, respectively. A total of 115 significant loci were detected through association mapping in three models (MLM, mrMLM, and FarmCPU), which explained 0.53%-19.4% of the phenotypic variations. Of them, 10 loci were repeatedly detected in different environments and models, one of which qBAD.A03-2 was verified as a stable QTL using a secondary segregation population. Totally, 1066 differentially expressed genes (DEGs) were identified between branch adaxial- and abaxial- sides from four extremely large or small BA/BD accessions through RNA sequencing. These DEGs were significantly enriched in the pathways related to auxin biosynthesis and transport as well as cell extension such as indole alkaloid biosynthesis, other glycan degradation, and fatty acid elongation. Four known candidate genes BnaA02g16500D (PIN1), BnaA03g10430D (PIN2), BnaC03g06250D (LAZY1), and BnaC06g20640D (ARF17) were identified by both GWAS and RNA-seq, all of which were involved in regulating the asymmetric distribution of auxins. Our identified association loci and candidate genes provide a theoretical basis for further study of gene cloning and genetic improvement of branch architecture.